Substitution of Mangrove Flour as a Food Functional Ingredient in Cookies - Tinda Yuvita; Oktaf Rina; Nurbani Kalsum (AIBPM Publisher, 2026)
Functional foods are increasingly becoming a focus in the development of food products that meet basic nutritional needs and provide additional health benefits. One food ingredient with the potential to become a source of functional food is mangrove flour, produced from the fruit of mangrove trees in coastal areas. Mangroves contain fiber, antioxidants, and bioactive compounds that can improve the nutritional quality of food products. Mangrove flour possesses significant potential to enhance the nutritional value of cookies, a popular bakery product, without compromising their sensory quality. This study aimed to evaluate the effect of mangrove flour substitution in cookie formulations. Variations in mangrove flour substitution were carried out at levels of 10%, 20%, 30%, 40%, and 50% and were tested based on color, taste, aroma, texture, and overall acceptability. The results showed that mangrove flour substitution had a significant impact on consumer preference, with the average score at 20% substitution for color, taste, and aroma. However, at higher substitutions, a decrease in preference was observed, especially for aroma and texture. Overall acceptability also decreased at substitutions exceeding 30%. These findings demonstrate the importance of balancing mangrove flour formulation in cookies to maintain optimal sensory quality